写出下图中Z1、Z2、Z3的逻辑函数表达式,并化为最简的”与-或”表达式,正确的是: 。[img=269x162]18038ab3e0caed6.jpg[/img]
A: [img=194x95]18038ab3ebe7bc5.jpg[/img]
B: [img=183x88]18038ab3f78ded0.jpg[/img]
C: [img=186x85]18038ab401b0af3.jpg[/img]
D: [img=186x85]18038ab40c7ad63.jpg[/img]
A: [img=194x95]18038ab3ebe7bc5.jpg[/img]
B: [img=183x88]18038ab3f78ded0.jpg[/img]
C: [img=186x85]18038ab401b0af3.jpg[/img]
D: [img=186x85]18038ab40c7ad63.jpg[/img]
举一反三
- 写出下图中Z1、Z2、Z3的逻辑函数表达式,并化为最简的”与-或”表达式,正确的是: 。[img=269x162]18035a2aeeb223c.jpg[/img] A: [img=194x95]18035a2afa3bbe0.jpg[/img] B: [img=183x88]18035a2b05dfe27.jpg[/img] C: [img=186x85]18035a2b0f59585.jpg[/img] D: [img=186x85]18035a2b1a2ad40.jpg[/img]
- 写出下图中Z1、Z2、Z3的逻辑函数表达式,并化为最简的”与-或”表达式,正确的是: 。[img=269x162]180396814cce3c7.jpg[/img] A: [img=194x95]1803968158c8980.jpg[/img] B: [img=183x88]180396816433577.jpg[/img] C: [img=186x85]180396816f5b3f0.jpg[/img] D: [img=186x85]180396817a0fe96.jpg[/img]
- 写出下图中Z1、Z2、Z3的逻辑函数表达式,并化为最简的”与-或”表达式,正确的是: 。[img=269x162]18036560a0da4d9.jpg[/img] A: [img=194x95]18036560abeee66.jpg[/img] B: [img=183x88]18036560b6e284b.jpg[/img] C: [img=186x85]18036560c0ebcf9.jpg[/img] D: [img=186x85]18036560cb1c1de.jpg[/img]
- 写出下图中Z1、Z2、Z3的逻辑函数表达式,并化为最简的”与-或”表达式,正确的是: 。[img=269x162]18036c0f210ee9b.jpg[/img] A: [img=194x95]18036c0f2bf89f4.jpg[/img] B: [img=183x88]18036c0f37f97ba.jpg[/img] C: [img=186x85]18036c0f43764e2.jpg[/img] D: [img=186x85]18036c0f4f1e988.jpg[/img]
- 写出下图中Z1、Z2、Z3的逻辑函数表达式,并化为最简的”与-或”表达式,正确的是: 。[img=269x162]18036f80e2202ee.jpg[/img] A: [img=194x95]18036f80ee4896a.jpg[/img] B: [img=183x88]18036f80facc579.jpg[/img] C: [img=186x85]18036f81055b7a9.jpg[/img] D: [img=186x85]18036f81114cd32.jpg[/img]